2008
DOI: 10.1007/s00264-008-0676-y
|View full text |Cite
|
Sign up to set email alerts
|

Irreducible dislocation of the hip in cerebral palsy patients treated by Schanz proximal femoral valgus osteotomy

Abstract: Palliative Schanz proximal femoral valgus osteotomy is considered a common option for treatment of irreducible hip dislocation in cerebral palsy. From 1992 to 2005, Schanz osteotomy was indicated on 55 occasions in 35 nonambulatory patients with the quadriplegic form of cerebral palsy aged 9-18. Postoperatively, the main emphasis focussed on clinical presentation, improvement of hip range of motion, and pain relief. X-rays were carried out at three, six, and 12 months postoperatively with subsequent average fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
2
15

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 22 publications
(26 reference statements)
0
22
2
15
Order By: Relevance
“…If the hip is symptomatic and unreconstructable, there is a choice of salvage procedures to obtain reasonable abduction and relief of pain. These include proximal femoral resection [49][50][51][52][53][54][55][56][57][58][59][60][61], prosthetic replacement of the hip [62][63][64][65][66][67][68][69][70], prosthetic interposition arthroplasty [71], valgus femoral osteotomy [72,73], a combination of valgus osteotomy and proximal femoral excision [55,57], and hip fusion [66].…”
Section: The Unreconstructable Hipmentioning
confidence: 99%
“…If the hip is symptomatic and unreconstructable, there is a choice of salvage procedures to obtain reasonable abduction and relief of pain. These include proximal femoral resection [49][50][51][52][53][54][55][56][57][58][59][60][61], prosthetic replacement of the hip [62][63][64][65][66][67][68][69][70], prosthetic interposition arthroplasty [71], valgus femoral osteotomy [72,73], a combination of valgus osteotomy and proximal femoral excision [55,57], and hip fusion [66].…”
Section: The Unreconstructable Hipmentioning
confidence: 99%
“…Only sitting tolerance was shown to improve in their study [11]. Schejbalova et al reported 98% pain relief in nonambulatory patients with irreducible dislocation of the hip treated by Schanz proximal valgus osteotomy, which is not a treatment option in ambulatory patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…-устранение или снижение болевого синдрома [27,34,35,36,37,38,39]; -устранение порочного положения бедра, возмож-ность его беспрепятственной мобилизации [27,28,34,40,41,42,43]; -улучшение условий ухода за пациентом, в том числе гигиены промежности [27,28,34,40].…”
unclassified
“…-артродез тазобедренного сустава [14,35]; -протезирование тазобедренного сустава [14,27,40,44,45]; -проксимальная артропластическая резекция бе-дра [41,42]; -вальгизирующая остеотомия проксимального от-дела бедра в сочетании с резекцией головки или без таковой [26,37,39,46].…”
unclassified
See 1 more Smart Citation